If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18m + 27 = 2m + -3 Reorder the terms: 27 + 18m = 2m + -3 Reorder the terms: 27 + 18m = -3 + 2m Solving 27 + 18m = -3 + 2m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-2m' to each side of the equation. 27 + 18m + -2m = -3 + 2m + -2m Combine like terms: 18m + -2m = 16m 27 + 16m = -3 + 2m + -2m Combine like terms: 2m + -2m = 0 27 + 16m = -3 + 0 27 + 16m = -3 Add '-27' to each side of the equation. 27 + -27 + 16m = -3 + -27 Combine like terms: 27 + -27 = 0 0 + 16m = -3 + -27 16m = -3 + -27 Combine like terms: -3 + -27 = -30 16m = -30 Divide each side by '16'. m = -1.875 Simplifying m = -1.875
| -4-6x=-64 | | y-5y= | | m(m+4)(m-7)=0 | | 3(3x-1)=4(4x-1) | | 4s+8=12 | | x+11=314.86 | | -14(9+19p)=3066 | | 12(x-7)=60 | | X^2+x=2 | | 4p^2-5pq= | | 252=x+.8x | | 3(y+7)=4(y-2) | | 3m-8m=10 | | 4=p+14 | | 3x^2(4x+5)(x-6)=0 | | -6(2p+2)-24=4(3p+3) | | 4p^4-5pq= | | 1-10x=-319 | | -3p+5p+4=6 | | 6n-6=18 | | 4x^2+12x+9= | | 12n-24=-14+28 | | (5x+15)(5x+15)=45 | | 6x^2+5x=4 | | -19(1-3k)-5k=553 | | 5.4x-4.3(x-1)=5.7 | | 2x^5-15x^4+32x^3+6x^2-60x=0 | | .875r+.25=.75+.375r | | 2(c-5)=3(c-6) | | 14(x-7)=42 | | -15+4x=-6(x+8)-x | | (8x+4)(9x^2+8x+2)=0 |